TAXATION OF E-SPORTS IN DEVELOPING WORLD - Orçun Avcı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Today, great progress is being made in information technology with the digital age. However, technological opportunities have started to be used extensively in many areas. The game industry has also been affected by this situation. With electronic sports (e-sports), the sports concept of the new digital world has begun to change. E-sports has become an important organization for both the players and the game industry. E-sports, where interest is increasing day by day, has led to the formation of a large economic market. The world benefits greatly from this market. However, there are some problems with taxing e-sports in the world. It is seen that there is no clarity on how e-sports will be taxed. The existing problem in this regard causes a decrease in the tax revenues of the countries and the emergence of international tax problems. The aim of this study is to provide information about e-sports in the developing world and to make suggestions on various examples of taxation. As a result of the study, it was determined that there are weaknesses in taxing e-sports around the world. Especially the absence of tax legislation regarding e-sports and the existence of a legal gap in taxation could seriously damage the tax systems of countries.